1980
DOI: 10.1111/j.1365-2125.1980.tb04794.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of salicylate during chronic aspirin therapy.

Abstract: 1. The effects of chronic administration of aspirin in therapeutic doses (3.9 g/day) on plasma and salivary salicylate levels were studied in eight subjects. 2. The urinary excretion profile for free salicylic acid and metabolites of salicylate were examined. 3. Plasma and salivary salicylate levels declined significantly after peak levels were achieved between days 3 and 10. 4. The decline in plasma and salivary salicylate levels may be due to an induction of a metabolic pathway such as salicylurate formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 15 publications
4
16
0
Order By: Relevance
“…In the absence of other explanations, the decrease in plasma salicylate concentrations has been attributed to induction of the formation of salicyluric acid. Furst et al (1977) observed a significant increase in the Vmax for salicylurate formation from 0.92 mg kg-1 h-1 to 1.36 mg kg-' h-1, after only 3 days of oral aspirin therapy in 26 healthy subjects, while Rumble et al (1980) observed a nonsignificant increase in the urinary output of salicylurate during chronic dosing. Day et al (1983Day et al ( , 1988 suggested that the induction process was time-limited, with no further increase in Vmax after 2 weeks.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…In the absence of other explanations, the decrease in plasma salicylate concentrations has been attributed to induction of the formation of salicyluric acid. Furst et al (1977) observed a significant increase in the Vmax for salicylurate formation from 0.92 mg kg-1 h-1 to 1.36 mg kg-' h-1, after only 3 days of oral aspirin therapy in 26 healthy subjects, while Rumble et al (1980) observed a nonsignificant increase in the urinary output of salicylurate during chronic dosing. Day et al (1983Day et al ( , 1988 suggested that the induction process was time-limited, with no further increase in Vmax after 2 weeks.…”
Section: Introductionmentioning
confidence: 88%
“…Box 252C, Hobart, Tasmania 7001, Australia state drug concentrations, studies in healthy subjects have reported a significant decline in steady-state plasma salicylate concentration during chronic administration of therapeutic doses of aspirin (Miiller et al, 1975;Olsson 1983;Rumble et al, 1980). Many questions about the actual nature of this observed decline and associated efficacy also remain unanswered.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations